White blood cell counts can predict 4-year cardiovascular disease risk in patients with stable coronary heart disease: a prospective cohort study - Jiang, Wencai; Huang, Gang; Du, Jinfeng; Yang, Hanxuan; Zhou, Shiheng; Dai, Dayin; Tang, Kai; Fang, Lingxiao; Wang, Xiao; Deng, Xuejun (Frontiers in Cardiovascular Medicine, 2024)
BACKGROUND: The prevalence of cardiovascular disease has increased sharply in the Asian population, and evaluation of cardiovascular events risk with stable coronary heart disease is still challenging. The role of white blood cell (WBC) count to assist clinical decision making in this setting is less clear. OBJECTIVES: This study sought to evaluate the prognostic meaning of WBC count among patients with stable coronary heart disease. METHODS: The Asian participants (n = 1933) obtained from the prospective STABILITY (Stabilization of Atherosclerotic Plaque by Initiation of Darapladib Therapy) trial,which included 15 828 patients with stable coronary heart disease with 3 to 5 years’ follow‐up on optimal secondary preventive treatment. WBC count was measured at baseline. Associations between WBC count and cardiovascular outcomes were evaluated by Cox regression analyses with multivariable adjustments. Haematologic emergencies in patients may lead to potential bias. RESULTS: In lower WBC count quartiles, patients had lower-risk clinical profiles. Higher WBC count was associated with greater event probabilities for cardiovascular death, major cardiovascular event or all-cause death. In Cox regression models, for the primary outcomes, WBC counts were an independent predictor of major adverse cardiovascular events (OR = 2.445, 95% CI 1.427–4.190, P = 0.001). For the secondary outcomes composite of all-cause death, cardiovascular death, myocardial infarction, stroke and hospitalization for heart failure, WBC counts were significantly predictive of events in a similar magnitude (OR = 1.716, 95% CI 1.169–2.521, P = 0.006). CONCLUSIONS: In patients with stable coronary heart disease, higher count of WBC were associated with heightened risk for the primary outcomes or the secondary outcomes.